The Influence of Capital Intensity, Inventory Intensity, and Profitability on Tax Aggressiveness with Debt Levels as a Moderating Variable - Riski Ayu Fitriani; Menik Indrati (Yayasan Ilomata, 2023)
This study's objective was to analyze the impact of capital intensity, inventory intensity, and profitability on tax aggressiveness, with debt level serving as a moderator. This study includes three independent factors, namely Capital Intensity, Inventory Intensity, and Profitability; one dependent variable, namely Tax Aggressiveness; and one moderating variable, namely Debt Level or Leverage. In this study, 17 firms out of a total observation of 45 companies with research objects on the LQ45 company index listed on the Indonesia Stock Exchange (IDX) from 2017 to 2021 met the inclusion requirements. According to the findings of this study, capital intensity has a beneficial effect on tax aggression. The variable inventory intensity has no positive impact on tax aggression. The unpredictable profitability has a favorable impact on tax aggressiveness. The association between capital intensity and tax aggression cannot be moderated by the variable of leverage. The association between inventory intensity and tax aggression cannot be moderated by the variable of leverage. The variable of leverage moderates in a positive way the association between profitability and tax aggression. This research can also be used to encourage investors and shareholders to receive financial statement information offered by companies with greater care when making investment decisions. For companies to be able to determine positive policies that can maintain business continuity and can meet the expectations of shareholders will carry out tax aggressiveness.